Advances in Design, Simulation and Manufacturing III : Proceedings of the 3rd International Conference on Design, Simulation, Manufacturing: The Innovation Exchange, DSMIE-2020, June 9-12, 2020, Kharkiv, Ukraine – Volume 1: Manufacturing and Materials Engineering /: Proceedings of the 3rd International Conference on Design, Simulation, Manufacturing: The Innovation Exchange, DSMIE-2020, June 9-12, 2020, Kharkiv, Ukraine – Volume 1: Manufacturing and Materials Engineering. (2020) - Unknown
No abstract available